Thiel's embalming method: review of the literature and our institute's experience - Lidija Kocbek; Mateja Rakuša (Acta Medico-Biotechnica, 2021)
Purpose: We aimed to present one of the best researched methods of cadaver preservation, Thiel's method, and share our own 9–year experience in comparison with that of the literature.Methods: Thiel's embalming method uses intravascular injection of a solution combined of several chemicals, such as water–based mixtures of monopropylene glycol, ammonium nitrate, potassium nitrate, sodium sulfite, boric acid, chlorocresol, formaldehyde, ethanol, and morpholine. Initial perfusion via the carotid and femoral arteries is followed by immersion in a cadaver storage basin in embalming solution for at least 4–6 months. After this, cadavers are stored in plastic bags in refrigerators and are used for months to years.Results: Since 2008, we have successfully embalmed 16 cadavers using Thiel's method. Due to the beneficial characteristics of this method, Thiel's embalmed cadavers have become an important part of our education and research. Despite initial technical difficulties, we managed to upgrade the method and assure better long–lasting preservation.Conclusions: Thiel embalmed cadavers resemble realistic living bodies and serve as an appropriate model for teaching and research.